CAP-italizing on the Strengths of Learners: The effect of Contract Activity Package versus traditional instruction on the achievement of regents level students in 8th grade social studies - Ed.D, Roger Bloom, (Social Science Learning Education Journal, 2017)
Teachers are most effective when they match their instruction to a studentâs learning style (Dunn & Dunn, 1993).Â It is very important for students to be engaged in activities that build on their perceptual and cognitive strengths.Â After all, traditional instruction, compromising of teacher-directed information intake, only works for a percentage of students.Â In the present quasi-experimental study, 16 students in a suburban middle school on Long Island were taught eighth grade social studies through a learning styles Contract Activity Package.Â The other 16 students in the control group were taught through traditional instruction.Â Using a contract activity package, students were assigned behavioral objectives for each lesson, activity alternatives, reporting alternatives for each behavioral objective, and team learning activities.Â Pre-tests and post-tests were administered to both groups of students to measure the effects of both forms of instruction.Â The students who learned through contract activity packages achieved proportionally similar gains from pre- and post-tests as compared with the students who learned through traditional instruction.Â Additionally, males and females who learned through contract activity packages achieved proportionally similar gains from pre- and post-tests.Â Based on the findings, the incorporation of learning styles strategies such as contract activity packages can serve as an alternative method of teaching for students that are not being fully serviced through traditional instruction.